2020
DOI: 10.1002/iub.2385
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from T regulatory cells relieve inflammatory bowel disease by transferring miR‐195a‐3p

Abstract: Previous studies have demonstrated the therapeutic effects of regulatory T (Treg) cells on inflammatory bowel disease (IBD), but the mechanism is not well-understood. Exosomes have been proposed as a novel mechanism underlying the action of Tregs. This study aimed to investigate the therapeutic effects of exosomes secreted by Treg cells (Treg-Exo) on IBD and to explore the underlying mechanism. Treg-Exo was isolated from BALB/c mouse spleen mononuclear cells and then injected into a murine model of IBD induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, EVs have been found to have immunosuppressive effects, such as suppressing the activation of DCs to induce immune tolerance and participating in regulatory T cell (Treg) activation [18] . Activated Treg also secretes exosomes containing miR-195-3p, targeting pro-apoptotic Caspase 12, to alleviate IBD in mice [70] . IEC-derived exosomes are crucial regulators among sections, mediating the modulation of resident immune cells.…”
Section: Extracellular Vesicles From Host Cells In Ibd-gimentioning
confidence: 99%
“…Furthermore, EVs have been found to have immunosuppressive effects, such as suppressing the activation of DCs to induce immune tolerance and participating in regulatory T cell (Treg) activation [18] . Activated Treg also secretes exosomes containing miR-195-3p, targeting pro-apoptotic Caspase 12, to alleviate IBD in mice [70] . IEC-derived exosomes are crucial regulators among sections, mediating the modulation of resident immune cells.…”
Section: Extracellular Vesicles From Host Cells In Ibd-gimentioning
confidence: 99%
“…Liao et al (2020) showed that Treg exosomes alleviate the severity of IBD in mice challenged with dextran sodium sulphate by transferring miR-195a-3p into IECs. This miRNA inhibits apoptosis by targeting caspase-12, allowing cell proliferation and repair of the intestinal epithelial barrier [ 150 ].…”
Section: Intercellular Communication By Evs In Intestinal Homeostamentioning
confidence: 99%
“…133 Treg cell-derived exosomes can promote IEC proliferation, inhibit IEC apoptosis, and protect the intestinal barrier in IBD mouse model. 134,135 Granulocytic myeloid-derived exosomes can alleviate IBD by diminishing the proportion of Th1 cells, and promoting the expansion of Treg cells. 136 These immune cell-derived exosomes may be the new therapeutic intervention for IBD in the future.…”
Section: Dovepressmentioning
confidence: 99%